2017
DOI: 10.1590/0034-7167-2016-0059
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of enteroparasites in children from Ribeirão Preto, São Paulo, Brazil

Abstract: Since the area presents good conditions of environmental sanitation, health education programs should be implemented that emphasize hygiene procedures for the hands and for food and water to be consumed by the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
2
8
0
10
Order By: Relevance
“…In this study, we found a positivity rate of 27.9% for one or more intestinal parasites in children from Salvador, Bahia. This corroborates with other studies undertaken in Brazil that reported frequencies varying between 5% and 50% [25,26]. G. duodenalis infection is more common in the infant population than in adults, with especially high frequencies detected in daycare centers and schools [27].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found a positivity rate of 27.9% for one or more intestinal parasites in children from Salvador, Bahia. This corroborates with other studies undertaken in Brazil that reported frequencies varying between 5% and 50% [25,26]. G. duodenalis infection is more common in the infant population than in adults, with especially high frequencies detected in daycare centers and schools [27].…”
Section: Discussionsupporting
confidence: 92%
“…(28.2%) and G. duodenalis (11.0%) were the species more frequently found. Both have been previously identified at prevalences typically ranging between 1–33% and 7–51%, respectively, in other Brazilian regions including Minas Gerais [ 52 , 53 ], Rio Grande do Sul [ 54 ], Santa Catarina [ 55 ] and São Paulo [ 56 , 57 ]. Blastocystis carriage was homogeneously distributed among all age groups investigated.…”
Section: Discussionmentioning
confidence: 99%
“…One should notice that, in a study conducted in the same region here researched to identify the prevalence of intestinal parasitic infections in a population of 233 children aged from 3 to 12 years, a high prevalence of parasitoses was found (57.5%), being Giardia lamblia the most found parasite (28) . This finding reinforces the need for implementing health education actions in this population, such as the one developed in this study.…”
Section: Discussionmentioning
confidence: 76%